Photoactive antimicrobial coating based on a PEDOT-fullerene C60 polymeric dyad - Reynoso, Eugenia (2021)
A photostable and photodynamic antimicrobial surface was successfully obtained and applied to photoinactivate microorganisms. This approach was based on the synthesis of a fullerene C60derivative (EDOT-C60) where fullerene C60is covalently linked to 3,4-ethylenedioxythiophene (EDOT) through a 1,3-dipolar cycloaddition reaction. This dual-functional monomer bears an EDOT center connectedviaan alkyl chain to a fullerene C60moiety. In this structure, EDOT acts as an electropolymerizable unit that allows the film formation over conducting substrates, while fullerene C60performs the photodynamic antimicrobial activity. Electrochemical polymerization of EDOT was used to obtain stable and photodynamic polymeric films (PEDOT-C60) in a controllable procedure. Cyclic voltammetry and UV-visible spectroscopy studies showed that the fullerene C60units were not altered during the electropolymerization process, obtaining surfaces with high fullerene content. Photobleaching measurements demonstrated that the electropolymerized films were highly photostable. Moreover, photodynamic properties ofPEDOT-C60were compared with fullerene C60and showed that electrodeposited films were able to generate reactive oxygen species (ROS) through the two photomechanisms, producing singlet molecular oxygen (type II) and superoxide radical anion (type I). All studies demonstrated that fullerene C60moieties covalently attached to the polymeric matrix mainly conserve the photodynamic characteristics. Hence, photodynamic action sensitized byPEDOT-C60was assessedin vitroagainstStaphylococcus aureus. The photosensitized inactivation by the electropolymerized films on bacteria suspensions produced >99.9% reduction inS. aureussurvival. Fluorescence microscopy experiments withS. aureusadhered to thePEDOT-C60surface showed a complete microbe annihilation. Also, the eradication of biofilms formed onPEDOT-C60surfaces resulted in a photokilling >99.9% after visible light irradiation. Our results demonstrated that these antimicrobial photodynamic polymeric films are a promising and versatile platform to photoinactivate microorganisms and to obtain photostable self-sterilizing surfaces.